Natural farming: A socio-ecological approach for sustainable livelihood - Chandel, Ashu; Kumar, Rakesh; Shankar, S Vishnu; Chandel, Rajeshwar Singh; Gupta, Rakesh Kumar; Kumar, Pramod (Indian Farming, 2023)
Himachal Pradesh is the only state in India where the government has achieved significant progress in creating academic programs and procedures to implement natural farming at the community level. Natural farming technique is a cutting-edge approach to agriculture that places a focus on sustainability and traditional methods. The technique uses little tillage, growing sequential legume and pulse crops, and utilizing local farm bio-resources. Additionally, it promotes the preservation of soil, water, and biodiversity resources. Concern over the negative environmental effects of conventional agricultural methods, such as the use of synthetic fertilizers and pesticides, soil erosion, and biodiversity loss, has grown in recent years. Natural farming promotes ecologically sustainable farming methods that are advantageous to farmers and the environment as a whole as a solution to these issues. This case study focuses on Shimla fruit growers who have demonstrated a high net return on adopting natural farming crop combinations over conventional farming including, apple + French bean + vegetables (`5,81,867) in rainy (kharif) season and apple + pea (`2,2042.2), apple + pulses + vegetables (`21,926.4) and apple + pea + vegetables (`20,140.3) in winter (rabi) season over conventional farming.